Aves aquáticas da área de proteção ambiental carste de Lagoa Santa: ecologia e conservação - Paula Fernanda Albonette de Nóbrega (2015)
This study aims to inventory the existing waterbird in the Environmental Protection Area Karst of Lagoa Santa (APA Karst); to understand its seasonal pattern of occurrence associating it to the characteristics of the seasonal lake system where it is inserted; to diagnose the environmental impacts in the region and its influence on the waterbird; and ultimately, gather the necessary information to propose the designation of the area as a Ramsar site. The research results might assist decision making processes to better preserve the area while bringing greater visibility to the region. To do so, the thesis is organised in six chapters, presented as articles, and an appendix. Chapter 1 presents the result of the waterbird inventory, indicating seasonal variations happening at the APA Karst and the birds sensitivity levels accordingly to environmental changes. Chapter 2 brings the record of two new species found in Minas Gerais State. The relationship between waterbird species richness and abundance, and the characteristics of the seasonal lake system of APA Karst are explored in Chapter 3. In chapter 4 waterbird pattern of occurrence and its seasonal variation is described, indicating variability associated factors. Chapter 5 presents a categorization of Lagoa Santas lake system from the regions existing environmental impacts viewpoint, associating the meeting of waterbird in APA Karst to these impacts. Ultimately, Chapter 6 presents a proposal for the designation of APA Karst Lagoa Santa as a Ramsar site. The appendix consists of the Field Guide of Waterbirds of Environmental Protection Area Karst of Lagoa Santa.